Hak Asasi Manusia Mahasiswa dalam Konteks Kebebasan Berpendapat di Kampus - Lifira Naila Salsabila; Khansa Kanastri Santoso; Usiono Usiono (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Regarding freedom of expression on campus, student human rights are very important to maintain academic freedom and freedom of expression on campus. The aim of this research is to examine how students perceive their human rights in relation to freedom of expression on campus. Qualitative research is a research methodology used in research. In-depth interviews with students were used to collect data, which was then collected by document analysis and reading relevant literature. The selection of respondents deliberately took into account the various perspectives and backgrounds they represent. Students view freedom of expression as a fundamental aspect of university life. They argue the right to free speech encourages discussion, introspection, and the sharing of ideas, all of which promote the growth of universities and society. This study highlights how students view their human rights in relation to freedom of expression on campus. The research conclusions can serve as a basis for improving the defense and implementation of students' human rights on campus as well as investigating the possibility of encouraging more inclusive discourse and teaching.